2007
DOI: 10.1007/s00467-007-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Treating severe Henoch-Schönlein and IgA nephritis with plasmapheresis alone

Abstract: The aim of our study was to determine the outcome of children with severe Henoch-Schönlein nephritis (HSN) and immunoglobulin A (IgA) nephritis (IgAN) treated with early plasmapheresis alone. Children with acute renal impairment, heavy proteinuria or both and histology greater than grade 3 were treated with early plasmapheresis alone. Glomerular filtration rate (GFR) estimated from plasma creatinine (eGFR), urine albumin:creatinine ratio (UA/UC) and blood pressure 2 weeks after treatment and were measured at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…This contradiction between these studies may be explained by the fact that initial plasma exchange may have further improved renal function in the investigation by Lundberg et al (20). The rationale behind these results, which has had favorable findings in some earlier reports on moderate to severe IgAN, is to rapidly delete circulating IgAcontaining immune complexes (22).…”
Section: Rituximab For Improvement Of Renal Function In Iganmentioning
confidence: 94%
“…This contradiction between these studies may be explained by the fact that initial plasma exchange may have further improved renal function in the investigation by Lundberg et al (20). The rationale behind these results, which has had favorable findings in some earlier reports on moderate to severe IgAN, is to rapidly delete circulating IgAcontaining immune complexes (22).…”
Section: Rituximab For Improvement Of Renal Function In Iganmentioning
confidence: 94%
“…Retrospective studies of children with crescentic HSP nephritis have demonstrated improvement in those treated with TPE alone [77,78] and in combination with medical immunosuppression [79], although no prospective data exist. Neither HSP nor IgA nephropathy is a recommended indication for TPE at this time [3].…”
Section: Other Glomerulonephritismentioning
confidence: 99%
“…1) The relationship between the severity of initial clinical and histological signs and the long-term prognosis [1][2][3][4][5]; 2) The correlation between chronicity score and time elapsed between clinical onset of kidney involvement and renal biopsy [10]; 3) The possible rapid evolution of crescentic glomerular lesions to complete glomerulosclerosis [11]; 4) A worse evolution when treatment is delayed even shortly [12][13][14][15]; 5) CKD developing years after apparent complete resolution [1,12].…”
Section: )mentioning
confidence: 99%
“…However, PE is not recommended in cases of ANCAassociated crescentic glomerulonephritis with moderate increases in plasma creatinine values only because no adequate RCT has yet been performed. In HSPN, PE alone has been used with success in two series of pediatric patients [13,14] presenting with acute renal function impairment, heavy proteinuria or nephrotic syndrome and a histological grade of ≥III [14] or equal to V [13]. At last review, after 4 [14] and 10 years [13], 13 of 14 [14] and six of nine patients [13], respectively, had a normal GFR and complete or almost complete resolution of other renal symptoms.…”
Section: Comment On Pementioning
confidence: 99%
See 1 more Smart Citation